Synthesis and Antibacterial Activity of Some 3-Acylamino-2-Azetidinones - Siddieg El-Shafie, Faiza (Asian Journal of Chemistry, 2010)
3-Amino and 3-acylamino 2-azetidinones were synthesized. Their antibacterial activity against gram negative, gram positive and β-Iactamase producing bacteria were estimated. Compounds (16) and (17) with a –COOH group onto the N1-phenyl substituent showed rather better activity against gram-negative and gram-positive bacteria.